PRELIMINARY SCREENING OF PHYTOCHEMICALS AND ANTIPROLIFERATIVE AND ANTI-INFLAMMATORY PROPERTIES OF THESPESIA POPULNEA (L.) SOLAND LEAF EXTRACTS - Kb, Megha; Cheriyamundath, Sanith; Madassery, Joseph; Kk, Elyas (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Plant-derived bioactive molecules are providing infinite opportunities for new drug development as they possess a wide range of actions against diseases with lesser side effects. The present study is made to analyze the qualitative phytochemicals and to evaluate in vitro antiproliferative and anti-inflammatory potentials of leaf extracts of Thespesia populnea. Methods: T. populnea leaf extracts were prepared sequentially according to the increasing polarity of the solvents, i.e., petroleum ether, chloroform, ethyl acetate, and methanol. Qualitative phytochemical analysis was performed to identify the chemical constituents of the extracts, and antiproliferative properties were evaluated against different cell lines using the 3-(4,5-dimethylthiazol-2-yl)-2,5 diphenyltetrazolium bromide assay. Bovine serum albumin anti-denaturation assay was done to identify the anti-inflammatory activity. Results: Phytochemical analysis of the extracts revealed the presence of alkaloids, terpenoids, glycosides, tannins, flavonoids, and phenolics. The chloroform extract (CHFE) of T. populnea has a dose-dependent antiproliferative effect against acute T-cell leukemia (Jurkat E6-1), prostate Grade IV adenocarcinoma (PC-3), mouse fibroblast (L-929), and monkey kidney normal (Vero) cells. Their inhibitory concentration 50% (IC50) values were found to be 35.73±0.94 μg/ml for Jurkat E6-1, 60.79±1.84 μg/ml for PC-3, 60.88±1.45 μg/ml for L-929, and 83.482±2.05 μg/ml for Vero, respectively. CHFE also displayed the anti-inflammatory potential. Conclusion: The chloroform leaf extract of T. populnea possesses potent antiproliferative and anti-inflammatory activity. These properties present in leaf extract may be explained by the presence of biologically active constituents.